FORMATION OF SOCIALLY RESPONSIBLE SUPPLY CHAIN MANAGEMENT BASED ON A BALANCED SCORECARD - Rustam Aslanzade (Izdevnieciba "Baltija Publishing", 2020)
The article is devoted to the substantiation of practical issues of implementing the principles of social responsibility in the company. An important part of any company's business is supply chain management. In modern business, this is a comprehensive activity for managing all incoming and outgoing flows of company resources. Implementation of supply chain management on the principles of social responsibility is possible only on the basis of a consistent and integrated approach. The article substantiates the possibility of introducing the principles of social responsibility in the activities of the company based on a balanced scorecard. The balanced scorecard includes four blocks: finance, customers, personnel, and internal business processes. Each block includes a specific list of indicators, which assess the degree of implementation of the principles of social responsibility. A system of specific indicators for companies that manufacture, supply and install climate equipment is proposed: Finance (level of profitability; turnover growth; amount of Freon used (reuse); the amount of a modern group of environmentally sustainable fluorine-free refrigerants used; reuse of materials and assessment of their value; etc.); Customers (percentage of safe refrigerants used in products; percentage of customer refusals from cooperation; percentage of regular customers (more than 2 transactions; more than 1 year of cooperation; etc.); Personnel (the volume and share of expenses for employees' certification; volumes and share of expenses for personnel development; volumes and share of expenses for stimulating employees); Internal business processes (accelerated service operations; reduction of time for placing orders; reduction of spoilage and waste; reduction of equipment maintenance and repair costs; reduction of time and costs of transportation operations; use of automated warehouse management systems; use of alternative energy sources; etc.). The proposed balanced scorecard allows the company to really build a green supply chain, which is an important competitive advantage.